أثر الاستثمارات الأجنبية على التنمية الاقتصادية في إثيوبيا 2021- في الفترة من 200: The impact of foreign investments on economic development in Ethiopia In the period from 2000-2021 - عثمان صالح محمد علي (Journal of North African Economies, 2025)
The research problem consisted of a basic question, which is to what extent Ethiopia succeeded in preparing its internal environment to attract foreign investments and then solve the problem of economic development? The research aims to identify the importance of foreign investment and the advantages it provides to the host countries, as well as the risks and threats to which this investment is exposed by developing countries, including Ethiopia, and to clarify the role that foreign investments play in the process of economic development in the State of Ethiopia, in order to obtain practical results. It is carried out by taking data on the Ethiopian economyand adopting descriptive analysis to test the hypotheses of the study, through which a set of results is reached, the most important of which is that foreign investments in Ethiopia played an important role in the process of economic development by providing added value to the national economy. Searching for an appropriate investment climate will attract foreign investments to Ethiopia.